A new species of Folsomia (Collembola: Isotomidae) from China - Ji, Ming; Ding, Yufeng; Chen, Jian-Xiu (Zootaxa, 2007)
A new species, Folsomia wanxianensis, from China (Chongqing) was described in the present paper. The new species shares some characters with F. albens Kaprus’ & Potapov 1999, such as the absence of ommatidia, sensillar formulae and small body size. However, it could be easily distinguished from F. albens by the number of laterodistal setae on the ventral tube and the number of setae on furca. It is also easily distinguished from all known species in the genus by the combination of the following characters: 4+4 laterodistal setae on the ventral tube, 10+10 dorsal setae on manubrium, 10–11 ventral and four dorsal setae on dens, and other features.